2014
DOI: 10.1007/s11357-014-9699-z
|View full text |Cite
|
Sign up to set email alerts
|

The skeletal muscle satellite cell response to a single bout of resistance-type exercise is delayed with aging in men

Abstract: Skeletal muscle satellite cells (SCs) have been shown to be instrumental in the muscle adaptive response to exercise. The present study determines age-related differences in SC content and activation status following a single bout of exercise. Ten young (22 ± 1 years) and 10 elderly (73 ± 1 years) men performed a single bout of resistance-type exercise. Muscle biopsies were collected before and 12, 24, 48, and 72 h after exercise. SC content and activation status were assessed in type I and type II muscle fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
120
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 93 publications
(143 citation statements)
references
References 60 publications
18
120
1
Order By: Relevance
“…There are numerous lines of evidence indicating resistance exercise, and long-term RT increase the prevalence of muscle satellite cells in humans (Dreyer et al 2006; Mackey and Robinovitch 2006; Petrella et al 2008; Verdijk et al 2009; Snijders et al 2014, 2016; Nederveen et al 2015). Correlative evidence supporting satellite cell–mediated myonuclear addition during human RT-induced myofiber hypertrophy gained traction in the mid-2000s (e.g., Olsen et al 2006; Petrella et al 2006, 2008) and studies reporting modest hypertrophy with no appreciable myonuclear addition (Petrella et al 2006, 2008; Verdijk et al 2009) fueled the concept of reaching a domain ceiling that led to a “demand” for nuclear addition.…”
Section: Muscle Stem (Satellite) Cell Activitymentioning
confidence: 99%
“…There are numerous lines of evidence indicating resistance exercise, and long-term RT increase the prevalence of muscle satellite cells in humans (Dreyer et al 2006; Mackey and Robinovitch 2006; Petrella et al 2008; Verdijk et al 2009; Snijders et al 2014, 2016; Nederveen et al 2015). Correlative evidence supporting satellite cell–mediated myonuclear addition during human RT-induced myofiber hypertrophy gained traction in the mid-2000s (e.g., Olsen et al 2006; Petrella et al 2006, 2008) and studies reporting modest hypertrophy with no appreciable myonuclear addition (Petrella et al 2006, 2008; Verdijk et al 2009) fueled the concept of reaching a domain ceiling that led to a “demand” for nuclear addition.…”
Section: Muscle Stem (Satellite) Cell Activitymentioning
confidence: 99%
“…However, recent work has shown that type II muscle fibre-specific SC content and function declines with increasing age [13,14]. In accordance, it has been hypothesized that the age-related dysfunction of SC plays a major role in impaired muscle regeneration and loss of muscle mass with aging.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of new myonuclei to existing muscle fibres represents an essential step in the maintenance and remodelling process of skeletal muscle. Hence, a reduction in SC number and/or function has been hypothesized to play a critical role in the development or progression of muscle fibre atrophy with age …”
Section: Introductionmentioning
confidence: 99%